2020
DOI: 10.1111/iej.13328
|View full text |Cite
|
Sign up to set email alerts
|

Post‐treatment endodontic pain following occlusal reduction in mandibular posterior teeth with symptomatic irreversible pulpitis and sensitivity to percussion: a single‐centre randomized controlled trial

Abstract: AimThis randomized, prospective, controlled trial assessed the effect of occlusal reduction on post‐treatment endodontic pain and medication intake following root canal treatment of mandibular posterior teeth with symptomatic irreversible pulpitis with sensitivity to percussion treated in two visits.MethodologyThree hundred and eight patients were randomly assigned into two equal groups according to whether occlusal reduction was done or not (n = 154). For all patients, root canal treatment was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…A standardized study protocol can aid in eliminating the confounding effects of intraoperative and postoperative variables on the use of pulpal medicaments ( Ahmed et al, 2020 ). Therefore the present investigation was intended as a randomized, double-blind clinical trial with a 1:1 allocation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A standardized study protocol can aid in eliminating the confounding effects of intraoperative and postoperative variables on the use of pulpal medicaments ( Ahmed et al, 2020 ). Therefore the present investigation was intended as a randomized, double-blind clinical trial with a 1:1 allocation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experienced moderate‐to‐severe preoperative pain that was either spontaneous or that lingered after patient's intake of cold beverages or foods. For preoperative pain assessment, patients were asked to record the maximum pain they felt spontaneously or after provocation by cold beverages/foods within the past 24 h prior to the endodontic visit (Ahmed et al, 2020; Nusstein & Beck, 2003) on a 0–10 Numerical Rating Analogue Scale (NRS) anchored by two extremes: ‘0’ indicating ‘no pain’ and ‘10’ indicating ‘worst pain felt’ and categorized as follows: 0 = none, 1–3 = mild, 4–6 = moderate and 7–10 = severe (Hjermstad et al, 2011). Before initiating the treatment, each patient rated her/his initial pain by marking the number that represented their pain level after being trained to use the scale.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Patients were randomized into groups with and without occlusal reduction, undergoing two-visit RCTs. Results indicated that occlusal reduction significantly reduced pain at 12 and 24 hours post-instrumentation, decreasing moderate-to-severe pain risk by 40% at 12 hours [ 48 ].…”
Section: Reviewmentioning
confidence: 99%